2015
DOI: 10.1093/schbul/sbv124
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Study of Glutamate in the Anterior Cingulate and Hippocampus in Schizophrenia

Abstract: Glutamate concentrations in schizophrenia deviate from controls and show associations with disease severity. A higher concentration of hippocampal glutamate in schizophrenia compared to controls is shown. The association between ACC and hippocampus glutamate concentrations in patients with schizophrenia suggests an abnormal coupling of excitatory systems compared to controls as predicted by previous glutamate models of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 68 publications
2
34
0
1
Order By: Relevance
“…Higher frontal Glx/Cr levels may predict poorer antipsychotic medication response(23). In medicated SCZ patients, glutamate is decreased(24) or unchanged(15) in ACC, decreased in PFC(25), and possibly decreased in hippocampus(24,26). Glx is also reduced in ACC(27) and mPFC of chronic patients, but not EC-SCZ or ultra-high-risk (UHR-SCZ) patients(28).…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Higher frontal Glx/Cr levels may predict poorer antipsychotic medication response(23). In medicated SCZ patients, glutamate is decreased(24) or unchanged(15) in ACC, decreased in PFC(25), and possibly decreased in hippocampus(24,26). Glx is also reduced in ACC(27) and mPFC of chronic patients, but not EC-SCZ or ultra-high-risk (UHR-SCZ) patients(28).…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Interestingly, alpha power was correlated with glutamate concentrations within the pACC, a factor that is known to be altered in schizophrenia (Gallinat, McMahon, Kühn, Schubert, & Schaefer, 2015;Mouchlianitis et al, 2015;Smesny et al, 2015)). A second study then showed that levels of spontaneous activity within the right temporoparietal junction (rTPJ) prior to stimulus onset, as measured with fMRI, determined whether an ambiguous sound would be experienced as the person's own name or not (Pengmin Qin et al, 2016).…”
Section: Abnormal Temporal and Spatial Structure In The Dmn And Ego Dmentioning
confidence: 99%
“…Therefore, there is an urgent need to improve pharmacotherapy of negative symptoms. Beside the dopaminergic system, dysfunctional glutamatergic neurotransmission has strongly been implicated in the etiology of schizophrenia, [1][2][3] particularly a hypofunction of the N-methyl-d-aspartate-receptor (NMDAR). 4 As NMDAR hypofunction is especially associated with negative symptoms, 5 the NMDAR is continuously discussed as being a promising target for the introduction of new medications.…”
Section: Introductionmentioning
confidence: 99%